1998
DOI: 10.1177/00030651980460030701
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Psychodynamics of Suicide

Abstract: This paper presents results from an empirical study of four key psychodynamic concepts (self-directed aggression, object loss, ego functioning disturbance, pathological object relations) of suicidal behavior. The sample consists of hospitalized psychiatric patients following a suicide attempt (attempters: n = 52) and demographically similar hospitalized psychiatric patients with no history of suicidal behavior (controls: n = 47). The study was designed to ascertain whether attempters differed from matched psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 18 publications
1
24
2
1
Order By: Relevance
“…Titelman, 2006). Kaslow et al (1998) and Leichsenring (2004) have documented the object-relations dynamics of suicidality in empirical research that is comparable to this study. The obliteration of intimate relatedness from consciousness in the lack-of-attachment phenomena brings into focus aggression as a dimension of suicidality.…”
Section: Features Of the Suicide Clustersupporting
confidence: 74%
“…Titelman, 2006). Kaslow et al (1998) and Leichsenring (2004) have documented the object-relations dynamics of suicidality in empirical research that is comparable to this study. The obliteration of intimate relatedness from consciousness in the lack-of-attachment phenomena brings into focus aggression as a dimension of suicidality.…”
Section: Features Of the Suicide Clustersupporting
confidence: 74%
“…The connection betweeti aggression towards oneself (suicide) and aggression towards others (violence) has been proposed by psychodynamic theorists (5,77,78). Subsequently, aggression was considered a distinguishing factor between those who did and did not commit suicide (79), with serotonergic dysregulation appearing to mediate this process (80).…”
Section: History Of Violent Actsmentioning
confidence: 99%
“…Research supports the role of dynamic and developmental factors in understanding suicidal patients [5,11,26]. Exploring the transfer and processing of counter…”
Section: Discussionmentioning
confidence: 75%
“…Empirical studies that aimed at testing the object-relational view of suicidal behavior concluded that object-loss (i.e. a more significant history of past and recent losses) could better explain suicidal behavior than self-targeted anger, maladaptive defenses or primitive object representations [25,26].…”
Section: Introductionmentioning
confidence: 99%